Effect of Problem-Based Learning Supported by PLEXA Media on the Mathematical Creative Thinking Skills of Fifth-Grade Elementary School Students - Rima Kusuma Dewi; Cucun Sunaengsih; Maulana Maulana (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
The increasing complexity of 21st-century challenges requires students to develop creative thinking skills to generate solutions to everyday problems. However, prior studies indicate that students' mathematical creative thinking remains limited due to low interest in solving math problems, dependence on teacher-given examples, and minimal effort to explore alternative problem-solving strategies. This study examined the effect of PLEXA (Problem Explorer Data)-assisted Problem-Based Learning (PBL) on fifth-grade students' mathematical creative thinking skills, using a quasi-experimental design with three nonequivalent groups (pretest-posttest). The sample comprised 122 fifth-grade students from three A-accredited public elementary schools in Cimalaka Subdistrict, Sumedang Regency: Experimental Group I (PLEXA-assisted PBL, n=49), Experimental Group II (PBL without media, n=43), and a control group (conventional learning, n=30). The research instrument, a mathematical creative thinking test, was validated through limited (n=6) and broad (n=55) pilot tests; 12 of 13 items were valid (Cronbach's alpha = 0.906, very high reliability). Data were analyzed using Shapiro-Wilk, Levene's, t-test, Wilcoxon, N-Gain, Pearson, Spearman, coefficient of determination, and Kruskal-Wallis tests. Results showed PLEXA-assisted PBL had the largest effect on mathematical creative thinking (41.47%), followed by PBL without media (38.19%) and conventional learning (30.91%). PLEXA-assisted PBL therefore has a significant effect on fifth-grade students' mathematical creative thinking skills.